2010
DOI: 10.1007/s11248-010-9399-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bt genetic engineering on indirect defense in cotton via a tritrophic interaction

Abstract: We present a tritrophic analysis of the potential non-intended pleiotropic effects of cry1Ac gene derived from Bacillus thurigiensis (Bt) insertion in cotton (DeltaPine 404 Bt Bollgard® variety) on the emission of herbivore induced volatile compounds and on the attraction of the egg parasitoid Trichogramma pretisoum (Hymenoptera: Trichogrammatidae). Both the herbivore damaged Bt variety and its non-Bt isoline (DeltaPine DP4049 variety) produced volatiles in higher quantity when compared to undamaged plants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Our findings are consistent with those of other studies that have identified VOCs emitted by cotton (McCall et al, 1994;Loughrin et al, 1995;Paré and Tumlinson, 1998;Röse et al, 1998;Rodriguez-Saona et al, 2003;Hegde et al, 2011;Moraes et al, 2011). Our chemical analyses revealed that herbivore feeding caused increases in the total emission of volatile compounds, as reported previously (Paré and Tumlinson, 1996;Röse et al, 1996), with the type of feeding damage also affecting production.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of other studies that have identified VOCs emitted by cotton (McCall et al, 1994;Loughrin et al, 1995;Paré and Tumlinson, 1998;Röse et al, 1998;Rodriguez-Saona et al, 2003;Hegde et al, 2011;Moraes et al, 2011). Our chemical analyses revealed that herbivore feeding caused increases in the total emission of volatile compounds, as reported previously (Paré and Tumlinson, 1996;Röse et al, 1996), with the type of feeding damage also affecting production.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that boll weevils responded positively to VOCs released by cotton plants of the genotypes TB90 and Rubi, and that they preferred the volatiles emitted by herbivory-damaged plants compared to volatiles emitted by undamaged plants. In addition, boll weevil feeding on plants caused an increase in the total amount of VOCs produced, consistent with previous studies on other plants showing that elevated VOCs were released in response to herbivore damage from both specialists and generalists (Rodriguez-Saona et al, 2003;Moraes et al, 2011;Magalhães et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, it has been previously known that cotton varieties can differ in the quantity and sometimes in quality of VOCs emission and these changes may be due to herbivory and plant phenological stage (Loughrin et al., ; Magalhães et al., ). Also differences in cotton VOC emission could be a side effect of plant genetic engineering for insect resistance (e.g., Bt‐cotton) (Moraes et al., ) or conventional plant breeding for agronomic purposes, such as higher yield, what can have a direct impact on host plant location by herbivores such as the boll weevil.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental design should include several field plots in future comparative studies. One prospective subject could be examining whether the foraging behavior of parasitoid wasps are disrupted in Bt cotton plots in terms of plant-emitted VOCs compared to conventional cotton plots [55,56]. It is also interesting to study how the genetic engineering affect the indirect interactions between cotton aphid and other herbivores, which can be mediated by plant and/or generalist predators [64,65].…”
Section: Discussionmentioning
confidence: 99%